YIELD AND WATER USE EFFICIENCY OF IRRIGATED CUPUAÇU TREES UNDER THE CLIMATE CONDITIONS OF CASTANHAL-PA, BRAZILIAN AMAZON - Costa, Deborah Luciany Pires; Vieira, IGOR CRISTIAN DE OLIVEIRA [UNESP]; Teixeira, ERIKA DE OLIVEIRA; Silva, Matheus Yan Freitas; Velame, MARIA DE LOURDES ALCÂNTARA; DE SOUZA, PAULO JORGE DE OLIVEIRA PONTE (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2022)
Cupuaçu tree is a promising species for the sustainable development of Amazonian agriculture. However, it is still in the domestication phase and requires phytotechnical studies to optimize fruit production. The objective of this study was to evaluate the yield and water use efficiency (WUE) of cupuaçu trees under different levels of water availability in the municipality of Castanhal-PA. The experiment was performed between 2018 and 2020 during two harvests, using micro-sprinkler irrigation in a 0.3 ha plantation of the BRS-Carimbó cupuaçu cultivar. The experimental design was completely randomized, with four treatments and 10 replications. The treatments were: TS (without irrigation-rainfed), T50, T100, and T150, referring to 50%, 100%, and 150% of the reference evapotranspiration, respectively. Analysis of variance and comparison of means were performed by the Tukey test (p<0.05), in addition to regression analysis. The results showed better performance in response to T100, which had fruit production 68% higher than TS. The results of yield and WUE were adjusted by polynomial regression, with maximum WUE for T100 (2.615 kg ha-1 mm-1) and minimum for TS (1.105 kg ha-1 mm-1). Therefore, irrigation must be equal to 100% of the reference evapotranspiration in cupuaçu plantations.
PRODUTIVIDADE E EFICIÊNCIA DO USO DA ÁGUA DE CUPUAÇUZEIRO IRRIGADO NAS CONDIÇÕES CLIMÁTICAS DE CASTANHAL-PA, AMAZÔNIA BRASILEIRA
Keywords: climate; intercropping; irrigation; Theobroma grandiflorum (Willd. ex Spreng.) K.Schum; yield